Prospecting Phosphate Solubilizing Rhizobacteria for Enhanced Growth in Finger Millet - Kumari, Poonam; Netam, R. S.; Zhodape, Vinita; Thakur, Tripti (International Journal of Economic Plants, 2025)
The experiment was conducted in kharif, 2020 (July to October) at SG College of Agriculture and Research Station, Jagdalpur, Chhattisgarh, India to explore the phosphate solubilizing bacteria from finger millet rhizosphere. Thirty rhizobacteria from finger millet rhizosphere were screened for their in-vitro phosphate solubilizing potential on solid and liquid National Botanical Research Institute’s (NBRIP) media containing insoluble tricalcium phosphate by two methods: visual evaluation of solubilization zone around colonies (halo) and determination of solubilized phosphates in liquid medium by the colorimetric method of vanado-molybdate yellow. Nineteen isolates tested positive for P-solubilization on NBRIP-Bromophenol medium with P-solubilization index ranging from 1.53–2.55. Based on the results of halo method, 19 positive isolates were inoculated in liquid medium and periodically analyzed for P-solubilization by the colorimetric method and effect on pH of the media. In the liquid NBRIP media, the bacterial isolates showed phosphate solubilization ranging from 21.31–114.87 mg l-1. The liquid media with insoluble tricalcium phosphate turned from turbid to clear after rhizobacterial cultivation and reduction in broth pH was recorded. Screening of PSB isolates for IAA production revealed that 17 out of 19 isolates produced a pink halo with varied intensity around the colony immobilized on nitrocellulose membrane suggesting IAA production with halo diameter range of 1.1–2.9 cm. Five most potent phosphate solubilizing rhizobacterial isolates were selected to assess their effect on finger millet growth. The isolates significantly improved the plant growth in terms of plant height, root length, plant biomass and chlorophyll content compared to the control.